O11 Parents' experience of 'our baby & us' – simulation-based education for parents on a neonatal intensive care unit. (10th November 2020) - Brown, Sebastian; Williamson, Sarah; Johnson, Susan; Cawsey, Emma; Raiman, Clare; Stockley, Elizabeth; Holder, Gemma
Abstract : Background: Family Integrated Care is a model of healthcare used on neonatal units where parents are treated as 'true partners' in their child's care. 1 This has been shown to reduce parents' stress and anxiety, and improve babies' weight gain and rates of exclusive breast-feeding at discharge. 2 One of the four pillars of Family Integrated Care is Parent Education, and simulation can be a key tool for this. Summary of Work of 'Our Baby and Us': A simulation-based parent education programme was set up in 2018 on our Neonatal Intensive Care Unit (NICU). It is run by a multidisciplinary group and aims to cover key aspects of neonatal care, allowing parents to practice skills in a safe, non-judgemental environment, before taking this knowledge back to their baby. We run weekly sessions covering: 'Getting to know your baby' (encompassing preterm baby behaviours, signs of distress and appropriate developmental care) 'Caring for my baby' (nappy changes, washing, temperature checks) 'Kangaroo Care' (practising skin–to–skin with preterm manikins) 'Feeding my baby' (all aspects of naso/oro–gastric tube feeding) We have collected written feedback in the form of a short questionnaire assessing parent's confidence in skills pre- and post- each session, as well as enquiring about what is most useful and taking suggestions for improvements to the sessions. Summary of Results: We found that the majority of parent respondents felt the sessions were useful/very useful (figure 1 ). We have also found that in each of the sessions, almost all of the parents reported their confidence in providing that particular aspect of neonatal care had increased. We asked parents to rate their confidence on a 5-point scale from 'not very' to 'very' confident both before and after each session. In 'Getting to know your baby' mean confidence increased from 2.9 to 4.5 (n=22), in 'Caring for my baby' it increased from 2.4 to 4.1 (n=18), in 'Kangaroo Care' it increased from 2.7 to 4.6 (n=11) and for 'Feeding my baby' it increased from 2.4 to 4.1 (n=13). Discussion and Conclusions: This feedback shows that we are improving parents' confidence in providing care to their babies, and we are continuing to promote family integrated care, particularly to the families of our preterm babies. Recommendations: We are now focusing on maintaining our programme during Coivd-19 and adding a secondary course focussing on discharge preparation for parents. References: www.familyintegratedcare.com/about-ficare/accessed August 2020 Effectiveness of Family Integrated Care in neonatal intensive care units on infant and parent outcomes: a multicentre, multinational, cluster-randomised controlled trial. O'Brien K, et al. Lancet Child Adolesc Health. 2018 Apr;2(4):245–254